Genetic and mating system assessment of translocation success of the long‐lived perennial shrub Lambertia orbifolia (Proteaceae). Issue 5 (3rd June 2021) - Monks, Leonie; Standish, Rachel; McArthur, Shelley; Dillon, Rebecca; Byrne, Margaret; Coates, David
Abstract : There is an increasing need to establish populations of threatened plants in threat‐free habitat to prevent species extinction. The amount of genetic diversity in founding plants will influence whether the new population has the capacity to persist and evolve over time, and factors that influence the maintenance of genetic diversity, such as the mating systems, will also play a role in population persistence. We developed 13 nuclear microsatellite markers and used these to evaluate genetic diversity and mating system parameters of three translocated populations of two subspecies of Lambertia orbifolia, and compared these parameters to seven wild populations. Genetic diversity was maintained in the translocated population of L. orbifolia subsp. Scott River Plains, established using a single source population ( N ar  = 3.270 and H e  = 0.478 in translocated population; N ar  = 3.280 and H e  = 0.534 in wild populations), and maintained or increased in the two admixed translocated populations of L. orbifolia subsp. orbifolia ( N ar  = 3.115, 3.830 and H e  = 0.511, 0.635 in translocated populations; N ar  = 2.708 and H e  = 0.438 in wild populations) compared to wild populations of each subspecies. Mating system parameters were comparable between translocated and wild populations of L. orbifolia subsp. Scott River Plains indicating the likelihood of genetic diversity being maintained in future generations. However, there was increased selfing in translocated populations of L. orbifolia subsp. o rbifolia, suggesting suboptimal pollination and high values for the inbreeding coefficient in these admixed populations ( F is  = 0.474, 0.275), which may be an artifact of the Wahlund effect or from less fit (inbred) seedlings surviving ex situ propagation and translocation.